Malignant progression of invasive tumour cells seen in hypoxia present an accumulation of β-catenin in the nucleus at the tumour front - Demir, Resit; Dimmler, Arno; Naschberger, Elisabeth; Demir, Ilknur; Papadopoulos, Thomas; Melling, Nathaniel; Stürzl, Michael; Hohenberger, Werner (Experimental and Molecular Pathology, 2009)
Of all processes involved in tumour progression, local invasion and formation of metastases are the clinically most relevant but the scientifically least well understood at their molecular level. The loss of cell adhesion, then tumour cell migration with changes in the cytoskeleton, invasion and metastatic dissemination are the steps of the "metastatic cascade". The E-cadherin-catenin complex plays a key role in cell adhesion thus building the first step in malignant progression. In many epithelial cancers, E-cadherin is lost concomitantly with tumour progression. Thus β-catenin dissociates in the cytoplasm and accumulates in the nucleus as a transcription factor. Recent experimental progress has identified that tumour hypoxia not only induces tumour angiogenesis, but also modulates malignant progression to initiate tumour invasion and metastasis. It was hypothesised that hypoxia within tumours causes dysfunction of the E-cadherin-catenin complex with an accumulation of β-catenin in the nucleus and produces an invasive phenotype of tumour cells. For this purpose fertilized chicken eggs were incubated for ten days in normoxic conditions. Subsequently colon carcinoma cells (SW-480) were placed on the chorioallantoic membrane. During the following six days the eggs were incubated either in normoxic conditions or in stepwise decreasing hypoxic conditions. SW-480 colon carcinoma cells did not invade the epithelial layer in normoxic conditions. β-catenin was membrane bound or in the cytoplasm. The nuclei were regularly omitted. In contrast, an invasion through the epithelial layer into the mesoderm was already seen after three days when incubated in hypoxic conditions. β-catenin was membrane bound in non-invasive regions of the tumour nodule but there was an accumulation of β-catenin in the nucleus in the invasive tumour front. Hypoxia seems to be responsible for accumulation of β-catenin in the nucleus which is accompanied by a more invasive phenotype of tumour cells at the tumour front. © 2009 Elsevier Inc. All rights reserved.
Created from Fastlane, Scopus look-up
Keywords: Beta-Catenin; Chorioallantoic membrane; Hypoxia; Malignant progression